Violent minds : modernism and the criminal - Levay, Matthew (Cambridge, 2019)
"Just as cultural attitudes toward criminality were undergoing profound shifts in the late nineteenth and early twentieth centuries, modernist authors became fascinated by crime and its perpetrators, as well as the burgeoning genre of crime fiction. Throughout the period, a diverse range of British and American novelists took the criminal as a case study for experimenting with forms of psychological representation while also drawing on the conventions of crime fiction in order to imagine new ways of conceptualizing the criminal mind. Matthew Levay traces the history of that attention to criminal psychology in modernist fiction, placing understudied authors like Wyndham Lewis, Dorothy Sayers, Graham Greene, and Patricia Highsmith in dialogue with more canonical contemporaries like Joseph Conrad, Henry James, Dashiell Hammett, and Gertrude Stein. Levay demonstrates criminality's pivotal role in establishing quintessentially modernist forms of psychological representation and brings to light modernism's deep but understudied connections to popular literature, especially crime fiction"--